Effects of Current and Future Summer Marine Heat Waves on Posidonia oceanica: Plant Origin Matters? - Stipcich, Patrizia; Marín-Guirao, Lazaro; Pansini, Arianna; Pinna, Federico; Procaccini, Gabriele; Pusceddu, Antonio; Soru, Santina; Ceccherelli, Giulia (Frontiers in Climate, 2022)
Marine heat waves (MHWs), prolonged discrete anomalously warm water events, have been increasing significantly in duration, intensity and frequency all over the world, and have been associated with a variety of impacts including alteration of ecosystem structure and function. This study assessed the effects of current and future MHWs on the Mediterranean seagrass Posidonia oceanica performance, also testing the importance of the thermal environment where the plant lives. The effects of current MHWs were studied through a mensurative experiment in a cold and in a warm site (West and North-West Sardinia, Italy, respectively). Future MHWs effects were tested through a manipulative experiment using P. oceanica shoots collected from the cold and warm sites and transplanted in a common garden in front of a power plant (North-West Sardinia): here plants were exposed to heat longer in duration and stronger in intensity than the natural MHWs of the last 20 years, resembling the future scenario. Morphological (total # of leaves, maximum leaf length, and percentage of total necrotic leaf length per shoot) and biochemical variables (leaf proteins, carbohydrates, and lipids) were considered. Plants had similar sublethal responses in both the experiments for most of the variables, revealing that current and future MHWs had similar effect types, but different in magnitude depending on the intensity of the waves: in general, the number of leaves, the maximum leaf length and lipid content decreased, while the leaf necrosis and carbohydrates increased. However, also the origin of the plants affected the results, corroborating the hypothesis that the thermal context the plants live affects their tolerance to the heat. Overall, this study provided evidence about the importance of biochemical variations, such as carbohydrate and lipid levels, as potentially good indicators of seagrass heat stress.